Moringa oleifera Lam: caracterização molecular - Silva, Ronei Costa (2023)
Moringa oleifera Lam is a medium-sized tree belonging to the Moringaceae family, native to South Asia. It is popular in different parts of the world for its diverse nutritional and medicinal uses. Moringa is cultivated in various parts of the world and is well adapted in many regions, which provides greater variability of the species. Therefore, this study aimed to evaluate the genetic diversity among 10 genotypes of M. oleifera using 15 ISSR primers and 20 SSR primers. The experiment was conducted in a greenhouse at the Federal University of Espírito Santo (UFES) Alegre campus and at the Federal Institute of Espírito Santo, Alegre campus. The material was collected and donated. The seeds were sown in 290 cm³ tubes containing commercial substrate in order to generate seedlings to obtain plant material for molecular characterization. For the evaluation of genetic diversity, 10 genotypes of M. oleifera were analyzed. When the seedlings presented two to four pairs of definitive leaves, they were collected for DNA extraction using the Doyle and Doyle protocol adapted by the IAC. The genetic distance matrix was estimated through quantitative variables based on the Standardized Average Euclidean distance, and the genotypes were grouped using the Unweighted Paired Group Method using Arithmetic Averages (UPGMA) and validated using the cophenetic correlation coefficient. These procedures were performed for both SSR and ISSR primers. With the results obtained, it was possible to identify the formation of three distinct groups using the ISSR marker and the formation of four distinct groups using the SSR primers. In this work, it was possible to estimate the genetic variability among the studied genotypes, making it possible to make genotypes available for future M. oleifera genetic improvement programs. The ISSR primers were more efficient in discriminating the collected genotypes.